CONTENT ANALYSIS OF ENGLISH TEXTBOOK “INTERACTIVE ENGLISH” USED IN FIRST GRADE JUNIORHIGH SCHOOL IN 2013 CURRICULUM - Monica Septiani Tambunan (English Education Department at FKIP Nommensen University, 2019)
The objectives of this study are to find out the suitability of impressionistic and in-depth analysis in the textbook entitles